Hedging through Defense Diplomacy: Indonesia’s Non-Alignment in the Age of Emerging Technologies - Suminar, Sekar Hesti; Perwita, Anak Agung Banyu; Ramsi, Oktaheroe (Asian Journal of Science, Technology, Engineering, and Art, 2025)
Indonesia’s long-standing doctrine of a “free and active” foreign policy is increasingly reinterpreted in the 21st century as a strategic hedging approach, enabling the state to navigate intensifying great-power competition and rapid technological change. This study examines the emergence of defense diplomacy as a core instrument of Indonesia’s hedging strategy, allowing engagement with major powers and access to evolving defense technologies without compromising its non-aligned identity. Using a qualitative case study method, the research contrasts two key partnerships: the PT Len–Thales combat management system contract, representing Indonesia’s engagement with Western technology, and the ongoing Indonesia–India BrahMos missile negotiations, exemplifying diversification beyond traditional suppliers. The findings demonstrate that cultivating diverse, well-managed defense relationships mitigates overdependence on a single partner, enhances indigenous technological capacity, and advances strategic autonomy. This analysis argues that Indonesia’s hedging constitutes a contemporary articulation of non-alignment, reconciling normative commitments to sovereignty with pragmatic uncertainty management amid emerging technologies. By situating this dynamic within the broader framework of middle power diplomacy in the Indo-Pacific, the study underscores the growing relevance of defense diplomacy in safeguarding national interests in a fluid and contested geopolitical environment.